PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PROMOSI JABATAN STUDI KASUS PT PROGRESS DIECAST - Ardhy Lazuardy; Devi Resviani; Rendi Destriyawan; Tommy Mandaleo (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to model a support system for position promotion at PT. Progress Diecast. Identification of criteria and design has been included in the modeling Method used in designing the decision support system for the promotion of positions at PT. Progress Diecast is a Simple Additive Weighting (SAW) method with the help of Microsoft Excel Software as its processing and system model. The assessment criteria in the proposed decision support system consist of 3: Behavioral Criteria, Work Target Criteria, and Test Criteria. Each standard has indicators obtained from the interview results, then becomes an assessment of prospective employees who will be promoted to their positions. Behavioral Criteria have indicators: Discipline, Honesty, Leadership, Compliance, Responsibility, and Team Work. The Work Target Criteria have indicators: Analytical Thinking, Problem Solving and Decision Taking Skills, and Achievement Orientation. The test criteria have indicators, namely Technical Skills and Psychological Tests. The result of the Decision Support System model for the promotion of the position of a leader of the Quality Department at PT Progress Diecast alternative or selected employee candidates is Jajang with values final result 0.97198.